On the Boundary Condition and Related Instability in the Smoothed Particle Hydrodynamics - Ye, Chong; Mota, Philipe; Li, Jin; Lin, Kai; Qian, Wei-Liang [UNESP] (Iop Publishing Ltd, 2019)
In this work, we explore various relevant aspects of the Smoothed Particle Hydrodynamics regarding Burger?s equation. The stability, precision, and efficiency of the algorithm are investigated in terms of different implementations. In particular, we argue that the boundary condition plays an essential role in the stability of numerical implementation. Besides, the issue is shown to be closely associated with the initial particle distribution and the interpolation scheme. Among others, we introduce an interpolation scheme termed symmetrized finite particle method. The main advantage of the scheme is that its implementation does not involve any derivative of the kernel function. Concerning the equation of motion, the calculations are carried out using two distinct scenarios, where the particles are chosen to be either stationary or dynamically evolved. The obtained results are compared with those obtained by using the standard finite difference method for spatial derivatives. Our numerical results indicate subtle differences between different schemes regarding the choice of boundary condition. In particular, a novel type of instability is observed where the regular distribution is compromised as the particles start to traverse each other. Implications and further discussions of the present study are also addressed.
Keywords: hydrodynamic model; SPH algorithm; pair instability